Pemberdayaan Masyarakat Koperasi Budidaya Kambing dan Domba Guna Mewujudkan Kampung Cerdas Sosial - Agus Surono; Agung Subyakto; Suprapto; Nurlaili Humaidah; Nur Husodo; Daril Ridho Zuchrillah (I-Com: Indonesian Community Journal, 2024)
Goat and sheep cultivation has traditionally been implemented from generation to generation by breeders cultivating goats and sheep in the cooperative "Rukun Raharjo Sentosa" in Tanjungsari hamlet, Gunungsari Village, Beji District, Pasuruan Regency. The maintenance system implemented so far is a system for providing animal feed, a system for managing and utilizing goat and sheep manure, as well as a system for managing sheep wool. The ITS community service team conducted a focus group discussion with the management of the goat and sheep cultivation cooperative regarding the problems currently being faced, namely the limited availability of animal feed due to the long dry season and goat and sheep waste that is not managed properly. The aim and target of this service activity is to empower goat and sheep farmers to obtain quality feed and manure that is well utilized. By planning and realizing appropriate technology that suits these problems, the community service team and KKN students carry out outreach and assistance so that farmers can independently manage animal feed and manure waste well, thus creating a socially intelligent village.